2022
DOI: 10.3390/ijerph191710716
|View full text |Cite
|
Sign up to set email alerts
|

Big Five Traits as Predictors of a Healthy Lifestyle during the COVID-19 Pandemic: Results of a Russian Cross-Sectional Study

Abstract: The healthy lifestyle of people around the world has changed dramatically during the COVID-19 pandemic. The personality risk factors for these processes from around the world remain understudied. This study aimed to examine the associations of the Big Five traits with a healthy lifestyle during the COVID-19 pandemic. In a cross-sectional study, data from 1215 Russian university students were analyzed. Participants completed the Big Five Inventory-10 and Short Multidimensional Inventory Lifestyle Evaluation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…This result confirms a very high number of previous findings documenting that neurotic people are prone to distress and psychopathology, both in a variety of situations (Bogg and Roberts, 2013;Friedman and Kern, 2014;Strickhouser et al, 2017;Anglim et al, 2020) and also during the COVID-19 pandemic (Qian and Yahara, 2020;Kocjan et al, 2021;Kohút et al, 2021;Nikčević et al, 2021;Schmiedeberg and Thönnissen, 2021). This is also in line with COVID-19 data about stress and wellbeing of secondary school and university students (Staller et al, 2021;Iterbeke and De Witte, 2022;Quigley et al, 2022;Wang et al, 2022;Zolotareva et al, 2022). Moreover, the relation between students' Negative Emotionality and Despair was very strong and it was higher compared to the relation with the other four traits, again supporting previous COVID-19related findings (Kocjan et al, 2021;Bacon et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result confirms a very high number of previous findings documenting that neurotic people are prone to distress and psychopathology, both in a variety of situations (Bogg and Roberts, 2013;Friedman and Kern, 2014;Strickhouser et al, 2017;Anglim et al, 2020) and also during the COVID-19 pandemic (Qian and Yahara, 2020;Kocjan et al, 2021;Kohút et al, 2021;Nikčević et al, 2021;Schmiedeberg and Thönnissen, 2021). This is also in line with COVID-19 data about stress and wellbeing of secondary school and university students (Staller et al, 2021;Iterbeke and De Witte, 2022;Quigley et al, 2022;Wang et al, 2022;Zolotareva et al, 2022). Moreover, the relation between students' Negative Emotionality and Despair was very strong and it was higher compared to the relation with the other four traits, again supporting previous COVID-19related findings (Kocjan et al, 2021;Bacon et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research involving university students has already in part examined the role of the Big Five traits concerning coping (i.e., Anglim and Horwood, 2021 ; Audet et al, 2021 ; Sahinidis and Tsaknis, 2021 ; Staller et al, 2021 ; Quigley et al, 2022 ; Wang et al, 2022 ; Weiß et al, 2022 ; Zolotareva et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For Russian university students whose data were collected in March and April 2020, extraversion positively predicted a focus on: diet and nutrition, physical activity, stress management, and restorative sleep. Although it was negatively associated with substance abuse, it was also more likely to expose students to contracting COVID-19 [31]. In another study conducted during March and April of 2020, Greek research of university students found extraversion had little to no effect on student satisfaction with online learning [32].…”
Section: Wavementioning
confidence: 98%